2009
DOI: 10.1136/tc.2009.030544
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand smoke exposure (PM2.5) in outdoor dining areas and its correlates: Figure 1

Abstract: When individuals sit in outdoor dining venues where smokers are present it is possible that they will be exposed to substantial SHS levels. Significant increases in exposure were observed when monitors were located under overhead covers, and as the number of nearby smokers increased. The role of outdoor smoking restrictions in minimising exposure to SHS must be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 20 publications
5
47
2
1
Order By: Relevance
“…Experimental work has found that RSP levels were approximately halved for each doubling of distance from the point source,27 51 but approached ambient levels at distances >2 m 51. Based on regression modelling by Cameron, cigarettes smoked at distances >1 m from a monitor did not significantly predict overall PM 2.5 levels (p=0.261) 29. Outdoor SHS levels have been found to be roughly equal to or greater than indoor SHS levels at very close distances (<0.5 m) 27.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Experimental work has found that RSP levels were approximately halved for each doubling of distance from the point source,27 51 but approached ambient levels at distances >2 m 51. Based on regression modelling by Cameron, cigarettes smoked at distances >1 m from a monitor did not significantly predict overall PM 2.5 levels (p=0.261) 29. Outdoor SHS levels have been found to be roughly equal to or greater than indoor SHS levels at very close distances (<0.5 m) 27.…”
Section: Resultsmentioning
confidence: 98%
“…Cameron et al collected data within 1 m of active smokers at a convenience sample of 69 outdoor dining areas in Melbourne, Australia 29. Mean ambient levels were 8 µg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…These policies are also attracting attention from urban authorities who may be interested in 'healthy' city branding, and reducing litter and fire costs (Schneider et al, 2011). In particular, tobacco smoke pollution (TSP) has been found to contribute to outdoor air pollution as measured by fine particulate (PM 2.5 ) levels from work in Canada (Kennedy et al, 2007); the USA (Klepeis et al, 2007); Australia (in Perth (Stafford et al, 2010) and in Melbourne (Cameron et al, 2010)) and New Zealand . Further work in Canada found that smoking within nine metres of building entrances significantly contributes to raised PM 2.5 levels (Kaufman et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Repace (2005) conducted experiments outdoors in a circle of up to 10 smokers on the University of Maryland campus and estimated that particle concentrations were inversely related to distance from the smokers over distances from 1.5 to 5 m. smoke outdoors at waiting areas and patios of 5 restaurants and bars in downtown Athens, Georgia, and they found that PM 2.5 concentrations were associated with the number of smokers present and were a better marker of outdoor secondhand smoke than CO. Klepeis et al (2009) conducted 100 controlled experiments releasing a CO tracer gas and using up to 36 CO monitors outdoors to measure the outdoor "proximity effect"-the decrease in concentration with distance from a source, including the effect of winds. Cameron et al (2010) measured PM 2.5 concentrations outdoors at restaurant tables in Melbourne, Australia, and found that levels increased by an average of 27.3 mg/m 3 during the smoking period 1 m from a smoker, with a maximum peak of 484 mg/m 3 . López et al (2012) measured PM 2.5 and nicotine in indoor and outdoor hospitality sites in eight European countries, and Licht et al (2013) reviewed the research literature on studies measuring PM 2.5 concentrations from secondhand smoke outdoors.…”
Section: Introductionmentioning
confidence: 99%
“…St. Helen et al (2011) smoke outdoors at waiting areas and patios of 5 restaurants and bars in downtown Athens, Georgia, and they found that PM 2.5 concentrations were associated with the number of smokers present and were a better marker of outdoor secondhand smoke than CO. Klepeis et al (2009) conducted 100 controlled experiments releasing a CO tracer gas and using up to 36 CO monitors outdoors to measure the outdoor "proximity effect"-the decrease in concentration with distance from a source, including the effect of winds. Cameron et al (2010) Licht et al (2013) reviewed the research literature on studies measuring PM 2.5 concentrations from secondhand smoke outdoors. These studies of outdoor settings, although few in number, show that relatively high air pollutant concentrations can occur outdoors close to a smoker and that outdoor exposure can be significant.…”
mentioning
confidence: 99%